High cereblon expression is associated with better survival in patients with newly diagnosed multiple myeloma treated with thalidomide maintenance - Broyl, Annemiek; Kuiper, Rowan; van Duin, Mark; van der Holt, Bronno; el Jarari, Laila; Bertsch, Uta; Zweegman, Sonja; Buijs, Arjan; Hose, Dirk; Lokhorst, Henk M.; Goldschmidt, Hartmut; Sonneveld, Pieter (Blood, 2013)
Recently, cereblon (CRBN) expression was found to be essential for the activity of thalidomide and lenalidomide. In the present study, we investigated whether the clinical efficacy of thalidomide in multiple myeloma is associated with CRBN expression in myeloma cells. Patients with newly diagnosed multiple myeloma were included in the HOVON-65/GMMG-HD4 trial, in which postintensification treatment in 1 arm consisted of daily thalidomide (50 mg) for 2 years. Gene-expression profiling, determined at the start of the trial, was available for 96 patients who started thalidomide maintenance. In this patient set, increase of CRBN gene expression was significantly associated with longerprogression-free survival (P = .005). In contrast, no association between CRBN expression and survival was observed in the arm with bortezomib maintenance. We conclude that CRBN expression may be associated with the clinical efficacy of thalidomide. This trial has been registered at the Nederlands Trial Register (www.trialregister.nl) as NTR213; at the European Union Drug Regulating Authorities Clinical Trials (EudraCT) as 2004-000944-26; and at the International Standard Randomized Controlled Trial Number (ISRCTN) as 64455289.
prepublished online as BloodFirst Edition paper, December 11, 2012
Gesehen am 08.12.2020